Correction to: Extremity soft tissue coverage in the combat zone: use of pedicled flap transfers by the deployed orthopedic surgeon - Mathieu, Laurent; Plang, Soryapong; de l’Escalopier, Nicolas; Murison, James Charles; Gaillard, Christophe; Bertani, Antoine; Rongieras, Frédéric (Military medical research, 2021)
An amendment to this paper has been published and can be accessed via the original article.